Native Endophytes of Tripterygium wilfordii-Mediated Biotransformation Reduces Toxicity of Celastrol - Ma, Ping-yang; Geng, Wei-ling; Ji, Hong-yan; Yue, Bang-wen; Liu, Cheng; Wang, Sa; Jiang, Zhi-bo; Chen, Jing; Wu, Xiu-li (Frontiers in Microbiology, 2022)
Celastrol (1), obtained from the roots of Tripterygium wilfordii Hook F., is most likely to become an antitumor drug, but with severe cytotoxicity. Due to the lack of modifiable sites in the structure of celastrol, the structural diversity of the modified products obtained by synthesis in the previous studies is insufficient, which hinders the pace of its patent medicine. This study describes a method of microbial transformation to increase the modification site of celastrol and reduce its toxicity. The screening of endophytes from native plants was introduced in this context, which led to two novel stereoselective oxidation products such as S-16-hydroxyl celastrol (2) and A-ring aromatized S-16-hydroxyl celastrol (3), along with a rare 7,9-octadecadienoic acid ester of celastrol (4). Their structures were determined by extensive spectroscopic data analysis, especially 1D and 2D NMR. Compared with 1, compounds 3 and 4 exhibited similar antitumor activity in U251, A549, KG-1, and B16 cell lines. Compound 2 had slightly decreased antitumor activity when compared with compound 1. Furthermore, compound 2–4 showed lower cytotoxicity against BV-2 (about 21-fold lower, 2: 92.82 μM, 3: 34.25 μM, and 4: 74.75 μM vs. celastrol: 4.35 μM), and also identical trends against H9c2 and PC12 cell lines.